1971
DOI: 10.1111/j.1432-1033.1971.tb19692.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Phosphopyruvate Carboxylase to Tryptophan Metabolites and Metal Ions

Abstract: Tryptophan, administered to rats, inhibits gluconeogenesis, but increases the activity of hepatic phosphopyruvate carboxylase when assayed in vitro. Quinolinate, a metabolite of tryptophan, inhibits gluconeogenesis in perfused livers, and inhibits phosphopyruvate carboxylase in liver cytosol from tryptophan-treated rats but not from normal rats.Metal The elevated phosphopyruvate carboxylase activity in cytosol of tryptophan-treated rats was lowered in vitro by quinolinate to the same extent as was the activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

1973
1973
2003
2003

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 12 publications
(15 reference statements)
2
34
0
1
Order By: Relevance
“…It has been shown that administration of tryptophan to fasting rats results in the suppression of gluconeogenesis and enhancement of fatty acid synthesis in the liver (24). These phenomena have been partially interpreted as being caused by the inhibitory effect of quinolinate, which is produced from tryptophan, on phosphoenolpyruvate carboxykinase activity (25). Therefore it is likely that dietary fat would alter lipid and carbohydrate metabolism by increased quinolinate production.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that administration of tryptophan to fasting rats results in the suppression of gluconeogenesis and enhancement of fatty acid synthesis in the liver (24). These phenomena have been partially interpreted as being caused by the inhibitory effect of quinolinate, which is produced from tryptophan, on phosphoenolpyruvate carboxykinase activity (25). Therefore it is likely that dietary fat would alter lipid and carbohydrate metabolism by increased quinolinate production.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to hormones, divalent cations have been reported to stimulate Ppymvate carboxykinase activity (Snoke et al, 1971 ;Colombo and Lardy, 1981 ;Schramm et al, 1981;Schramm 1986;Lee et al, 1981 ;Nowak, 1986) by modifying transcription, although this subject is a matter of controversy (Maggini et al, 1993). Lardy and coworkers proposed a catalytic effect mediated by a metal-enzyme complex dependent upon a protein activator found in the hepatocyte cytosol (Bentle, 1976;Bentle and Lardy, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…V en ezia le et al [1967] have shown that the metabolite of L-tryptophan largely (but not completely) responsible for the anti-gluconeogenic action (PEP CK inhibition) of L-tryptophan, is quino linic acid -so that the compound quinolinic acid dihydrazide has actually two chemical moieties in the same molecule (quinolinic acid and hydrazine), each of which can separately inhibit PEP CK; this may very well account for its augmented action against tumors. Regarding the mechanism of action against PEP CK itself, there is evidence that this metal enzyme is activated in the intact liver by ferrous ion [Snoke et al, 1972] and it is known that quino linic acid in sufficient quantities will bind ferrous ion, forming a ferrous coor dination complex which inhibits the enzyme [Veneziale et al, 1967]. It has not been established whether the same iron complexing mechanism pertains to the hydrazides as a class, although it is known that sebacic dihydrazidean exceedingly good tumor inhibitor in the present study -is also an excellent chelating agent [Olin Corporation, personal commun.…”
Section: Discussionmentioning
confidence: 99%